Tests for normality in linear panel data models - Alejo, Javier (2015)
A new Stata command, xtsktest, is proposed to explore non-normalities in linear panel data models. The tests explore skewness and excess kurtosis allowing researchers to identify departures away from gaussianity in both error components of a standard panel regression, sepa- rately or jointly. The tests are based on recent results by Galvao, Montes- Rojas, Sosa-Escudero and Wang (2013), and can be seen as extending the classical Bera-Jarque normality test for the case of panel data.